2020
DOI: 10.1186/s40168-020-00838-5
|View full text |Cite
|
Sign up to set email alerts
|

Winter warming in Alaska accelerates lignin decomposition contributed by Proteobacteria

Abstract: Background: In a warmer world, microbial decomposition of previously frozen organic carbon (C) is one of the most likely positive climate feedbacks of permafrost regions to the atmosphere. However, mechanistic understanding of microbial mediation on chemically recalcitrant C instability is limited; thus, it is crucial to identify and evaluate active decomposers of chemically recalcitrant C, which is essential for predicting C-cycle feedbacks and their relative strength of influence on climate change. Using sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 63 publications
(90 reference statements)
4
36
0
Order By: Relevance
“…P. madseniana RP11 T also grows on phthalic acid [63], a major by-product of lignin degradation [89][90][91]. Indeed, our analysis demonstrated that the two major PHB-degrading phylotypes of Paraburkholderia predominated in studies of lignin degradation [40], and white rot decay [41], and were the principal degraders in all soil priming experiments where phenolic/aromatic compounds were utilized [10][11][12] (see Supplementary Results). All evidence indicates that Paraburkholderia, and close relatives, monopolize phenolic acid degradation in soil and co-metabolize SOC, resulting in priming of SOC stocks.…”
Section: Characteristics Of Phb-induced Soil Primingmentioning
confidence: 65%
See 4 more Smart Citations
“…P. madseniana RP11 T also grows on phthalic acid [63], a major by-product of lignin degradation [89][90][91]. Indeed, our analysis demonstrated that the two major PHB-degrading phylotypes of Paraburkholderia predominated in studies of lignin degradation [40], and white rot decay [41], and were the principal degraders in all soil priming experiments where phenolic/aromatic compounds were utilized [10][11][12] (see Supplementary Results). All evidence indicates that Paraburkholderia, and close relatives, monopolize phenolic acid degradation in soil and co-metabolize SOC, resulting in priming of SOC stocks.…”
Section: Characteristics Of Phb-induced Soil Primingmentioning
confidence: 65%
“…While glucose addition stimulated growth of Paraburkholderia, it also stimulates a wide diversity of microorganisms whose competitive interactions likely govern the magnitude and direction of the priming response. In contrast, additions of PHB (Figure 1), benzoate [11] or vanillin [10,12]…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations